Multimodal Analysis on Product Placement in Korean Drama: “Goblin” - Natalia Kristiva; Setefanus Suprajitno (Kata Kita: Journal of Language, Literature, and Teaching, 2020)
Many companies try to find innovative ways of reaching their target market and promoting their products. Product placement (PPL) is one of such innovative ways. PPL has become popular in marketing communication because the promotion in it is quite subtle. It happens because in PPL, the advertisement is integrated in the structure of the narratives of TV series or films where PPL takes place. Thus, PPL can skirt the negative view toward advertising. In this study, we examine how PPL convey advertising messages in Korean drama, Guardian: Great and Lonely God (Goblin). In so doing, by using multimodal theory we analyze the verbal and non-verbal communication practices found some scenes of the Korean drama, and the meaning of PPL semiotic resources in those scenes express. Our findings show that PPL conveys the advertising messages through the acting, the facial expression, and the shot of products.Keywords: Product Placement, Multimodal, Modes, Goblin, Verbal and Non-Verbal Communication